THE EFFECT OF ALCALASE ENZYME CONCENTRATION ON HYDROLYSIS OF FISH PROTEINTEMBAKUL (Periophthalamusminutus) - Fdw, Dhiky; Edison, Edison; Ilza, Mirna (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Mudskipper(Periophthalmusminutus) is the fish that lives in the mangrove forests. The fish was used as the raw material in this study. The purpose of this study was to determine the effect of adding the best concentration of alcalase enzymes to produce the protein hydrolyzate of mudskipper. The parameters observed were the value of non protein nitrogen (NPN) and protein content by using the Lowry’s method. The experimental design used was a non-factorial Completely Randomized Design (CRD). The treatment conducted was hydrolyzing the fish to produce the fish hydrolyzates protein at different concentration ofalcalase enzyme (1%, 1.5%, and 2%) for 1 hour at temperature 50 °C and pH 8.5. The results showed that the addition of alcalase enzyme1.5% produced the highest content of protein in fish flour at 86.56% (dw) and water at 8.85% (gw). The product was also showing the highest value of non-protein nitrogen (NPN) at 19.28% and Lowry's protein content at 16.96%. Keywords: Flour, parameter, proximate.